Biomekanika Cedera Otak Traumatik pada Kecelakaan Mobil Tunggal yang Melibatkan Empat Orang Penumpang - Prawiroharjo, Pukovisa; Karmila, Hanna; Mayza, Adre; Martono, Yesenia (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2022)
Traumatic Brain Injury (TBI) caused by traffic accidents remains the leading cause of death and disability. Based on data from the Global status report on road safety 2018, deaths caused by traffic accidents occur at a ratio of 18 per 100,000 populations. In traffic accidents, doctors are often asked to perform a verbal autopsy. When performing a verbal autopsy, knowledge of the mechanism of the accident is required to make it easier to analyse the pathomechanism and its implications for the patient. We present a case of an accident involving four passengers, which we reviewed related to the biomechanical process and implications for these four patients. The injuries that occur are influenced by various things such as the seating position in the vehicle, the mechanism of the collision, the vehicle's speed at the time of the collision and various other things, so the four have different injuries. Understanding the biomechanics of injuries in traffic accidents will help medical personnel to unravel the mechanism and sort out the possible causes of injuries